2010
DOI: 10.1186/1757-1146-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Split tendon transfers for the correction of spastic varus foot deformity: a case series study

Abstract: BackgroundOveractivity of anterior and/or posterior tibial tendon may be a causative factor of spastic varus foot deformity. The prevalence of their dysfunction has been reported with not well defined results. Although gait analysis and dynamic electromyography provide useful information for the assessment of the patients, they are not available in every hospital. The purpose of the current study is to identify the causative muscle producing the deformity and apply the most suitable technique for its correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
(33 reference statements)
0
42
0
1
Order By: Relevance
“…Arrows showed the two halves of the anterior tibialis tendon with a balanced position of the foot after the procedure the other hand, others have reported that the EMG data did not correlate well with the clinical findings and warned of the use of needle EMG while children walk [2,9]. In this study, the decision to perform the SPLATT procedure was based on the observational pre-operative gait analysis and the positive reflex withdrawal test [1,11]; however, the observers agreed that the deviations of the gait were rated fair to moderate [17], which could affect the surgical planning [9,11,18]. Furthermore, AT tendon overactivity could be a contributing factor of a failed outcome if a split PT transfer was employed [9].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Arrows showed the two halves of the anterior tibialis tendon with a balanced position of the foot after the procedure the other hand, others have reported that the EMG data did not correlate well with the clinical findings and warned of the use of needle EMG while children walk [2,9]. In this study, the decision to perform the SPLATT procedure was based on the observational pre-operative gait analysis and the positive reflex withdrawal test [1,11]; however, the observers agreed that the deviations of the gait were rated fair to moderate [17], which could affect the surgical planning [9,11,18]. Furthermore, AT tendon overactivity could be a contributing factor of a failed outcome if a split PT transfer was employed [9].…”
Section: Discussionmentioning
confidence: 81%
“…This difference may be due to the fact that children with GMFCS level 3 or more has a poorer ambulatory capacity to begin with so any visual assessment of their gait is variable [17] and will increase the chance of having an unpleasant outcome. Results of children with GMFCS levels 3 and 4 and levels 1 and 2 were similar; this would imply that the CCP did not have a sufficient follow-up time [11,16], thus the number of children may be too small to detect the difference between the groups. Concomitant knee and hip surgery and type of cerebral palsy can increase the deterioration of the gait during the follow-up period but the authors did not detect any significant association between these factors and a failed outcome [14].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations